Different volumes of injectate using electrostimulator and blinded techniques for brachial plexus block in dogs. (21st December 2013) - Riccó, C.; Shih, A.; Killos, M.; Henao‐Guerrero, N.; Graham, L.
Abstract : To compare different volumes of injectate using electrostimulator (ES)‐guided and blind brachial plexus blockade (BPB) techniques in dogs. Prospective, randomised, blinded study. Fifty‐eight healthy adult purpose‐bred beagle dogs. Animals were randomised into 4 groups based on the volume of methylene blue 0.1 per cent administered for BPB, three using ES technique: E1 (0.2 ml/kg, n=22), E2 (0.6 ml/kg, n=22), and E3 (1.0 ml/kg, n=14), and one using blinded technique B4 (1.0 ml/kg, n=14). After euthanasia, the axillary region was dissected and nerves identified by a blinded evaluator. Success was defined as 3/4 nerves stained, or presence of dye in the tissue immediately surrounding the plexus. There were no significant differences between groups when total nerve count, adjacent staining, success rate (92.8–100 per cent), or rate of haematoma were evaluated. The musculocutaneous nerve was significantly more targeted in B4 than E1 and E2, but not E3. Electrostimulator‐guided BPB using lower volumes of injectate had similar success rate as the blinded technique using higher volume, thus, lower volumes can be used without compromising success. When an ES is not available, the blind technique with 1 ml/kg is also acceptable. However, when performing an ES‐guided BPB, volumes as low as 0.2 ml/kg can be used. As volume is increased, the musculocutaneous nerve becomes more likely to be targeted.